Der Mythos Des Postfaktischen Und Die Grenzen Der Vernunft - Wuchterl, Kurt (Religija ir kultūra, 2015)
[full article, abstract in German; abstracts in English and Lithuanian] This article deals with the central philosophical problem that is left unsolved by the ending age of postmodernism – that there are no facts, but only interpretations (Nietzsche). In the context of digitization, there is often talk of the post-factual and alternative facts. Therefore, the article first attempts to clarify the relevant basic concepts. This is followed by a presentation of proof that the denial of the possibility of facts ends in a scepticism that is detached from life, including a lack of orientation, which has come into the general consciousness through global networking. Finally, it is shown that every form of life, with its naturalistic or generally philosophical reflections, must surely presuppose facts, which, properly speaking, can only be partly identified. This limitation is considered to be a boundary experience, which points to the necessity to recognize a certain “alterity” of reason and thus also leaves religious alternatives open. Der Mythos Des Postfaktischen Und Die Grenzen Der Vernunft Die Abhandlung kreist um das philosophische Zentralproblem, wonach es keine Fakten, sondern nur Interpretationen gibt (Nietzsche), das uns das gegenwärtig zu Ende gehende Zeitalter der Postmoderne ungelöst zurückgelassen hat. Dabei ist im Zusammenhang mit der Digitalisierung häufig vom Postfaktischen und von alternativen Fakten die Rede. Daher werden zuerst die relevanten Grundbegriffe geklärt. Anschließend folgt der Nachweis, dass die durch die Vernetzung der Welt in das allgemeine Bewusstsein gelangte Leugnung der Möglichkeit von Tatsachen in einer lebensfernen Skepsis samt der heutigen Orientierungs-losigkeit endet. Zum Schluss wird gezeigt, dass jede Lebensform samt deren naturalistischen oder allgemein philosophischen Reflexionen sicher Tatsachen voraussetzen muss, die man allerdings nur zum Teil identifizieren kann. Diese Einschränkung wird als Grenzerfahrung betrachtet, welche auf die Notwendigkeit eines Anderen der Vernunft verweist und damit auch religiöse Alternativen offen lässt.